The fibroblast growth factor receptor inhibitor, derazantinib, has strong efficacy in human gastric tumor models and synergizes with paclitaxel in vivo. Issue 4 (2nd April 2023) - McSheehy, Paul M.J.; Forster-Gross, Nicole; El Shemerly, Mahmoud; Bachmann, Felix; Roceri, Mila; Hermann, Norbert; Spickermann, Jochen; Kellenberger, Laurenz; Lane, Heidi A.
Abstract : Derazantinib (DZB) is an inhibitor of fibroblast growth factor receptors 1–3 (FGFR1–3), with additional activity against colony-stimulating-factor-1 receptor (CSF1R). We have profiled the activity of DZB in gastric cancer (GC) as monotherapy and combined with paclitaxel, and explored means of stratifying patients for treatment. The antiproliferative potency of DZB in vitro was quantified in 90 tumor cell lines and shown to correlate significantly with FGFR expression (<0.01) but not with FGFR DNA copy-number (CN) or FGFR mutations. In four GC cell lines in vitro, little or no synergy was observed with paclitaxel. In athymic nude mice, bearing cell-line derived xenografts (CDX) or patient-derived xenograft (PDX) GC models, DZB efficacy correlated highly significantly with FGFR gene expression ( r 2 = 0.58; P = 0.0003; n = 18), but not FGFR mutations or DNA-CN. In FGFR-driven GC models, DZB had comparable efficacy to three other FGFR inhibitors and was more efficacious than paclitaxel. DZB had dose-dependent plasma pharmacokinetics but showed low brain penetration at all doses. GC models (one CDX and six PDX) were tested for sensitivity to the combination of DZB and paclitaxel and characterized by immunohistochemistry. The combination showed synergy (5) or additivity (2), and no antagonism, with synergy significantly associated ( P < 0.05) with higher levels of M2-type macrophages. The association of strong efficacy of the combination in vivo with M2 macrophages, which are known to express CSF1R, and the absence of synergy in vitro is consistent with the tumor microenvironment also being a factor in DZB efficacy and suggests additional means by which DZB could be stratified for cancer treatment in the clinic.